The Effect of Servants’ Competence and Whistleblowing on Fraud Prevention in Fund Management - Rusma Rizal; Abdullah Rasjid; Agussalim Agussalim; Sukaria Darmawan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
Currently, people's demands for clean, fair, transparent, and accountable governance must be taken seriously and systematically. To be more accountable a strategy is needed in preventing fraud by maximizing the competency of the apparatus and whistleblowing. The purpose of this study was to determine and analyze the influence of Servants' Competence, Whistleblowing, on Fraud Prevention in Village Fund Management. This research method uses descriptive and verification surveys, and field data collection uses a questionnaire technique, this research is associative research, where in this study there are variables that are related and can influence other variables. The population of this research is village government officials in the Madang Suku II sub-district, East OKU district. Data processing using SEM PLS 3.0 analysis tool. The results of this study are: (1) there is an influence of Servants' Competence, on the prevention of fraud in the management of village funds, (2) there is an effect of whistleblowing on the prevention of fraud in the management of village funds.